Electrical signalling on Bt and non-Bt cotton plants under stress by Aphis gossypii - Pachú, Jéssica K.S.; Macedo, Francynes C.O.; Malaquias, José B. [UNESP]; Ramalho, Francisco S.; Oliveira, Ricardo F.; Franco, Flávia Pereira; Godoy, Wesley A.C. (Public Library of Science (PLoS), 2021)
Plants have developed various mechanisms to respond specifically to each biotrophic attack. It has been shown that the electrical signals emitted by plants are associated with herbivory stress responses and can lead to the activation of multiple defences. Bt cotton is a genetically modified pest-resistant plant that produces an insecticide from Bacillus thuringiensis (Bt) to control Lepidopteran species. Surprisingly, there is no study–yet, that characterizes the signalling mechanisms in transgenic cotton plants attacked by non-target insects, such as aphids. In this study, we characterized the production of electrical signals on Bt and non-Bt cotton plants infested with Aphis gossypii and, in addition, we characterized the dispersal behaviour of aphids to correlate this behaviour to plant signalling responses. Electrical signalling of the plants was recorded with an extracellular measurement technique. Impressively, our results showed that both Bt and non-Bt cotton varieties, when attacked by A. gossypii, emitted potential variation-type electrical signals and clearly showed the presence of distinct responses regarding their perception and the behaviour of aphids, with evidence of delay, in terms of signal amount, and almost twice the amount of Cry1F protein was observed on Bt cotton plants at the highest density of insects/plant. We present in our article some hypotheses that are based on plant physiology and insect behaviour to explain the responses found on Bt cotton plants under aphid stress.